2016
DOI: 10.1007/s10103-016-2056-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of low-level light therapy in supportive care for patients with breast cancer: review of the literature

Abstract: Breast cancer is the most common cancer in women worldwide, with an incidence of 1.7 million in 2012. Breast cancer and its treatments can bring along serious side effects such as fatigue, skin toxicity, lymphedema, pain, nausea, etc. These can substantially affect the patients' quality of life. Therefore, supportive care for breast cancer patients is an essential mainstay in the treatment. Low-level light therapy (LLLT) also named photobiomodulation therapy (PBMT) has proven its efficiency in general medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 86 publications
(102 reference statements)
0
40
1
1
Order By: Relevance
“…In the case of orthodontic pain, a systematic review showed positive effects of PBM in reducing intense pain since the first day of treatment . PBM has also been demonstrated to be an effective supportive therapy for the management of several side effects caused by breast cancer therapies, including radiodermatitis, lymphedema, chemotherapy‐induced peripheral neuropathy, osteonecrosis of the jaw and oral mucositis in paediatric patients, which all include a pain component .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of orthodontic pain, a systematic review showed positive effects of PBM in reducing intense pain since the first day of treatment . PBM has also been demonstrated to be an effective supportive therapy for the management of several side effects caused by breast cancer therapies, including radiodermatitis, lymphedema, chemotherapy‐induced peripheral neuropathy, osteonecrosis of the jaw and oral mucositis in paediatric patients, which all include a pain component .…”
Section: Introductionmentioning
confidence: 99%
“…Low-level laser therapy (LLLT) is being studied as a non-invasive treatment option for ORM (3, 5, 6). Initial clinical studies show promising results in the reduction of pain and improvement of the quality of life after LLLT treatment (712).…”
Section: Introductionmentioning
confidence: 99%
“…Prevention, early detection, and effective treatment are the key intervention points to increase the survival rate (1,2). About 1.7 million new breast cancer patients were diagnosed in 2012, representing approximately 12% of all cancer cases globally that year (3). Currently, breast cancer is classified into five major groups on the basis of molecular profiling.…”
Section: Introductionmentioning
confidence: 99%